The supply-side of environmental sustainability and export performance: The role of knowledge integration and international buyer involvement. Issue 4 (August 2017) - Li, Esther Lingyee; Zhou, Lianxi; Wu, Aiqi
Highlights: This study examines how an export supplier's market-oriented environmental sustainability leads to improved business performance. We reveal the roles of knowledge integration and international buyer involvement in understanding supply-side environmental sustainability. The results show that relationship efforts should be directed at developing integrative capacity for implementing proactive environmental strategy. This study contributes to the research of supply chain sustainability in a global context. Abstract: Most of previous studies seek to understand buyer perspectives in green supply chain relationships and devote inadequate attention to the strategic role of upstream suppliers. Drawing on a market-oriented approach to sustainability, this paper examines the enabling factors and processes that underpin how export suppliers from emerging economies leverage their strategic intent to develop knowledge integration capacity for achieving improved export performance. The results from a sample of Chinese exporters show that the relational capacity of knowledge integration mediates the performance impact of market-oriented environmental sustainability, and such a mediating process of leaning is further enhanced by international buyer involvement. We reveal that relationship efforts should be directed at developing integrative capacity involving key partners for implementing proactive environmental strategy in international business-to-business (B2B) markets. This study contributes to the research of supply chain sustainability in a global context.